1994
DOI: 10.1111/j.1365-2362.1994.tb01074.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of human vascular smooth muscle cell proliferation by lovastatin: the role of isoprenoid intermediates of cholesterol synthesis

Abstract: Abstract.Restenosis remains the largest single obstacle to the long-term success of invasive vascular interventions. Lovastatin, an HMG-CoA reductase inhibitor, has been shown to reduce myointimal hyperplasia in animal models of restenosis and in one clinical coronary restenosis trial. We have assessed the effect of lovastatin on the growth of cultured human vascular smooth muscle cells derived from saphenous vein and vascular graft stenoses. Lovastatin ( 2 p~) inhibited proliferation over 14 days in saphenous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
0
5

Year Published

2000
2000
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(44 citation statements)
references
References 42 publications
4
35
0
5
Order By: Relevance
“…Cerivastatin stock solution was prepared by dissolving the statin in Dulbecco's modified Eagle's medium (DMEM, Bio Whittaker, Walkersville, MD), followed by sterile filtration. Simvastatin stock solution was prepared after conversion from the inactive lactone form to the active open ring form (19), suspended in DMEM, and sterile filtered. Mevalonolactone (Sigma, St. Louis, MO) was converted to the open-ring product mevalonate, as with simvastatin.…”
Section: Statins and Isoprenoid Intermediatesmentioning
confidence: 99%
“…Cerivastatin stock solution was prepared by dissolving the statin in Dulbecco's modified Eagle's medium (DMEM, Bio Whittaker, Walkersville, MD), followed by sterile filtration. Simvastatin stock solution was prepared after conversion from the inactive lactone form to the active open ring form (19), suspended in DMEM, and sterile filtered. Mevalonolactone (Sigma, St. Louis, MO) was converted to the open-ring product mevalonate, as with simvastatin.…”
Section: Statins and Isoprenoid Intermediatesmentioning
confidence: 99%
“…Mevalonate and farnesol, but not cholesterol, reverse lovastatin-induced inhibition of human vascular smooth muscle cell proliferation (Munro et al 1994). In this study, we demonstrated that lovastatin-induced HL-60 cells death, DNA fragmentation, loss of mitochondrial transmembrane potential and cytochrome c release were attenuated by adding mevalonate.…”
Section: Discussionmentioning
confidence: 50%
“…Так, у дослідженні ASCOT спостерігалася достовірна різниця в частоті виникнення інфаркту міокарда та інсульту між підгрупами пацієнтів, які отримували аторвастатин та амлодипін (+ периндо-прил) або тільки амлодипін (+ периндоприл) [50]. Автори пояснювали це синергізмом дії амлодипіну (відновлення судинного тонусу, покращення функ-ції ендотелію, зменшення міграції гладком'язових клітин), периндоприлу (зменшення оксидативно-го стресу, якого зазнавав ендотелій, покращення функції ендотелію, зменшення агрегації тромбо-цитів, вазодилатація, зниження рівня біомаркерів атеросклеротичних ускладнень (D-димеру, цитокі-ну TNF-), зменшення апоптозу) та аторвастатину [34,41]. Вважається, що регрес ТКІМ при прийомі статинів частіше відбувається за рахунок зменшення товщини інтими, а при прийомі вазодилататорів -за рахунок зменшення товщини медії.…”
Section: клінічні дослідження / Clinicial Researchesunclassified